What is the most effective method to treat indirect carotid-cavernous fistula - Voldřich, Richard; Charvát, František; Beneš, Vladimír; Netuka, David (Neurosurgical review, 2022)
To review the most relevant treatment options for indirect carotid-cavernous fistulas (iCCF), cohorts of 20 patients or more published after 2000 were analyzed. Clinical and radiological outcomes, as well as embolization techniques and material, had to be clarified in the study to be considered. Statistical analysis was based on calculating the relative percentage of therapeutic methods or embolic material, followed by calculating parametric and nonparametric correlations. Some 22 studies and 1550 patients were included. Transvenous embolization (TVE) was used in 53% of the patients and was strongly associated with coiling (rw = 0.66, p = 0.0.0012; rs = 0.53, p = 0.0138), transarterial embolization (TAE) was preferred in 11% of the patients and was strongly linked to liquid embolics (rw = 0.44, p = 0.0434;rs = 0.64, p = 0.0018). A combination of TAE and TVE treatment was used in 7% and a combination of embolic materials in 13% of the patients. None of the endovascular techniques or embolization materials showed significant superiority over the others in clinical outcome and obliteration rate. Radiosurgery in 22% and mechanical compression in 5% of patients showed a lower obliteration rate (rw = - 0.48, p = 0.0254; rs = - 0.45, p = 0.0371). The clinical outcomes were comparable to endovascular treatment (EVT). The remaining 2% of the patients were treated by open surgery or a combination of EVT and radiosurgery. Transvenous coiling is the preferred EVT method for iCCF. However, comparable results may be accomplished with TAE using liquid. Radiosurgery may achieve a lower percentage of fistula occlusion, but the clinical results are equal to EVT.
Keywords: píštěle; Humans; lidé; Fistula